Boosting energy storage performance of ZnCoTe@NiCoSe2 with core-shell structure as an efficient positive electrode for fabrication of high-performance hybrid supercapacitors - Shiva Moraveji; Lida Fotouhi; Saeed Shahrokhian; Mohammad Zirak (Scientific Reports)
Abstract Transition metal chalcogenides are promising compounds in electrochemistry with different applications including energy conversion/storage devices due to their stability, different oxidation states, and highly active surface areas. In this work, ZnCoTe nanorods coated with NiCoSe2 as the shell have been synthesized by a two-step method. ZnCoTe@NiCoSe2 has an excellent specific capacity of 240 mAh g−1 at a current density of 2 A g−1 in a three-electrode system containing 3 M KOH electrolyte solution, which is much superior to each of the core and shell components of the constructed electrodes. Furthermore, a remarkable cycle life of 94% is obtained at a current density of 10 A g−1 after 5000 cycles, suggesting its long-term stability. The hybrid supercapacitor consists of ZnCoTe@NiCoSe2 and activated carbon as the positive and negative electrodes, respectively. In addition, ZnCoTe@NiCoSe2//AC (HSC device) showed 580 W kg−1 power density at an energy density of 57 Wh kg−1. Additionally, the device retained 90% of its initial capacitance after 5000 cycles. Eventually, considering the excellent electrical conductivities and large numbers of active sites, transition metal chalcogenides have been utilized as efficient electrodes for supercapacitor applications. This work introduces a method for the incorporation of zinc into the telluride matrix, which modulates the electronic structure, enhances intrinsic electrical conductivity, and increases the density of electroactive sites. Moreover, the engineered core–shell architecture of ZnCoTe@NiCoSe₂ provides a synergistic combination of high electrical conductivity, abundant active sites, and a well-organized hierarchical structure. These integrated features significantly boost charge storage performance and overall efficiency of the supercapacitor device.